You can stop humming now : a doctor's stories of life, death, and in between - Lamas, Daniela (New York : Little, Brown and Company, 2018)
"A critical care doctor's riveting stories about what it means to be saved by modern medicine"--Jacket flap.
You can stop humming now -- Ten percent -- Life on battery -- Nightmares after the ICU -- Emergence -- Where the bridge ends -- Networking for a kidney -- An unexpected adulthood -- How it begins.
Keywords: Lamas, Daniela -- Health; Critical care medicine -- United States -- Anecdotes; Physicians -- United States -- Biography; Emergency medicine; Intensive care units; Anecdotes; Biographies; Biography -- Anecdotes; Autobiographies; Anecdotes